Reading Achievement in Relation to Phonological Coding and Awareness in Deaf Readers: A Meta-analysis - Mayberry, Rachel I. (Oxford University Press, 2011)
The relation between reading ability and phonological coding and awareness (PCA) skills in individuals who are severely and profoundly deaf was investigated with a meta-analysis. From an initial set of 230 relevant publications, 57 studies were analyzed that experimentally tested PCA skills in 2,078 deaf participants. Half of the studies found statistically significant evidence for PCA skills and half did not. A subset of 25 studies also tested reading proficiency and showed a wide range of effect sizes. Overall PCA skills predicted 11% of the variance in reading proficiency in the deaf participants. Other possible modulating factors, such as task type and reading grade level, did not explain the remaining variance. In 7 studies where it was measured, language ability predicted 35% of the variance in reading proficiency. These meta-analytic results indicate that PCA skills are a low to moderate predictor of reading achievement in deaf individuals and that other factors, most notably language ability, have a greater influence on reading development, as has been found to be the case in the hearing population.